The Continuous Peat Water Treatment System To Lower Iron And Manganese as Live Media For Cyprinus carpio - Rahmaddani Saputra; M. Hasbi; Budijono ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This study was conducted in May 2014 in the of River Tarai, Tarai Bangunvillage, Kampar distric, Riau province. The purpose of this study was to reduce levelsof Fe and Mn with peat water treatment system that is continuous under appropriateregulation of government of number 82 year 2001, so that the processed water iscontinuously peat can be used as a medium of live Cyprinus carpio. Analysis ofwater samples conducted in laboratory peat Public Works Department Pekanbaru.The method used in this study is an experimental method to operate the packetprocessing tools peat water continuously. The research used filter media is zeolite,mangrove charcoal and coarse sand. The results of the peat water treatment systemsshowed a continuous decrease in the concentration levels of metals Fe is 0.0238 mg/L with an average 94.01% decrease effectiveness. The continuous peat watertreatment system also shows decrease in the concentration of Mn levels is 0.0034 mg/ L with an average decrease of 97.55% effectiveness. This value metal rate of Fe andMn after processed have as according to regulation of government of number 82 year2001. While testing the system using peat treated water continuously performedduring the 4 days can support rate of survival for Cyprinus carpio about 100%.Keywords : Peat water treatment, kontiniu, Iron, manganese, Cyprinus carpio